Shariah Compliance Analysis of Islamic Crowdfunding: Case Study of ethiscrowd.com - Ayu Yuningsih; Rifqi Muhammad (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
This paper aims to analyze the mechanism and implementation of crowdfunding on ethiscrowd.com and the evaluation of shariah compliance. Based on the parameters of shariah compliance proposed by Rosly (2010) it can be seen that the implementation of shariah crowdfunding of ethiscrowd.com has fulfilled the three parameters of shariah compliance namely ‘aqd, maqasid al-shariah and legal documentation. Meanwhile, in the case of financial and accounting reporting disclosed the ethiscrowd.com is not yet not fulfilling existing of regulations, where crowdfunding companies should publish detailed financial reports. The management of ethiscrowd.com only publishes project development reports funded by investors. This is because there is no specific provision for disclosing financial reporting and accounting for financial technology companies, especially those engaged in equity crowdfunding.